Evaluación del impacto de las políticas públicas del buen vivir en organizaciones agroproductivas solidarias de los cantones Jama y Tosagua - Peña Mero, Doris Marisol (2019)
The current problem within the economic system is the lack of recognition of popular economic practices and solidarity; for which we see the need to propose the recognition and potentialization of the principles that govern the popular and solidary economy within the agro-productive organizations. The General Objective of the research is: Evaluate the impact of public policies to demonstrate the fulfillment of the objectives of the National Plan of Good Living in Solidarity Agroproductive Organizations of the Jama and Tosagua cantons. Based on addressing the specific objectives, they have to provide theoretical information on the evaluation of the impact of public policies on Good Living, establish evaluation indicators to measure the impact of these policies, and make a diagnosis of the current situation of the solidarity agro-productive organizations in both cantons and identify the effects of public policies. In the methodological part, a series of elements are established in order to sustain quality research, such as types of research, methods, and techniques. Regarding the procedure, it is worth highlighting the relevant bibliographical sources with the purpose of complementing the research, the design of a survey that was applied by the people who work in the Solidarity Agro-productive Organizations, the identification of evaluation indicators and the use of techniques to evaluate public policies through the application of software and make a comparison of the effects of public policies based on obtaining each of the data.